ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA KONFEKSI “BOROSCLOTH” SEMARANG - Andre Akbar Wiguna; Augusty Tae Ferdinand (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
Along with the growth and development of confection business in the city of Semarang which increased significantly. More and more confection offers its services. Especially on Boroscloth's confection that offers clothing-making services. Increasing competition between confection to sell their products, causing in decreased sales of Boroscloth confection. Boroscloth confection must be able to use the best marketing strategy to stay afloat. The purpose of this study is to determine the magnitude of the influence of Product Design, Product Quality, and Competitive Price variables on Purchase Decision which is expected to increase the percentage or volume of Boroscloth product sales. Product Design, Product Quality, and Competitive Price as independent variables; brand image as intervening variable; and Purchase Decision as the dependent variable. The population used in this study was a customer who had used a Boroscloth confection service. Sampling technique used in this research is by purposive sampling. This research hypothesis testing using the data of 100 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS) version 24.The result of this study indicate that variable product quality positively affect to brand image. Then, variable competitive prices, brand image, and product design are positively affect to purchase decision.